The tidal station management application (PAS) - Mundirin Mundirin; Joko Prasetiana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The development of a geospatial information system is very necessary in providing basic data to be used as a single reference in national development planning and disaster management such as InaTEWS (Indonesia Tsunami Early Warning System. Tide Gauge Stations or Indonesia Tide Gauges (InaTides) is a collection of tide stations that produce data and managed by the Geospatial Information Agency (BIG), formerly known as Bakosurtanal. In 2019, 138 tidal stations were built, but they are still recorded manually in the form of maintenance during high tide. This is an obstacle in finding problems that arise in tidal operations. Therefore, to realize the availability of an ideal data series, a more structured, systematic and efficient management of tidal stations is needed. Use the PHP and MySql programming languages ​​in managing the database. With this application, it is expected to be a solution tidal management becomes more structured, systematic, efficient which is well documented.